Does waste feed from salmon farming affect the quality of saithe (Pollachius virens L.) attracted to fish farms?. (16th January 2020) - Uglem, Ingebrigt; Toledo‐Guedes, Kilian; Sanchez‐Jerez, Pablo; Ulvan, Eva Marita; Evensen, Tor; Sæther, Bjørn Steinar
Abstract: Salmon farms attract large amounts of wild fish, which prey on uneaten feed pellets. The modified diet of the wild fish aggregating at salmon farms may reduce the flesh quality of the fish, influencing the local fisheries. We compared the quality of saithe ( Pollachius virens ) captured near (farm associated—FA) or more than 5 km away (un‐associated—UA) from salmon farms in Norway. The fish were captured during summer, autumn and spring using two commercial fishing methods (jigging and bottom nets). Overall, the fillet quality of FA saithe was good, although it was clearly reduced for almost 10% of the catch. Moreover, the quality of the FA saithe was significantly reduced compared with UA saithe, but the differences were small. Our results also showed that fish caught with jigging had better quality than fish caught with nets, and that fish that died in the nets were of lower quality than fish that were alive after hauling. There was no clear variation among seasons in fillet quality. Although no major and overall differences in quality were found between FA and UA saithe, reduced quality for even a modest proportion of the fish may influence the value of the total catch.